Effect of adding different organic acids for fermentation on the quality of Sichuan Paocai - HUANG Yuli, GE Lihong, GUO Caifu, YANG Menglu, MEI Yuan, LAI Haimei, ZHAO Nan (Zhongguo niangzao, 2025)
The effects of adding organic acids on the fermentation process, quality and flavor of radish Paocai were investigated, by determining the physicochemical indexes, colour, texture, organic acid composition and volatile flavor substances of fermented radish Paocai with 0.089 mol/L addition of lactic acid, acetic acid and citric acid as well as without organic acids addition as control (CK). The results showed that after 5 d of fermentation, compared with the CK group, the reducing sugar contents in the acetic acid group was significantly reduced (P<0.05), and the nitrite contents in each organic acid group was significantly reduced (P<0.05). The b* values of the lactate and acetic acid groups significantly increased (P<0.05), the hardness and chewiness of the citric acid group significantly reduced (P<0.05), the chewiness of the acetic acid group was significantly reduced (P<0.05), and the brittleness was significantly increased (P<0.05). The total acid content and organic acid composition of the citric acid group changed greatly, while the organic acid composition of the lactic acid group was more abundant. Lactic acid group and citric acid group have more similar volatile flavor compounds, which were more conducive to the production of ester volatile flavor components. In summary, the addition of lactic acid had the optimal overall effect on radish Paocai.